POLEMIK “AHLI BID’AH” DALAM WACANA ULŪMUL HADĪṠ: Evaluasi Ibnu Ḥajar al-‘Asqalāny Terhadap Status Riwāyat al-Mubtadi’ - dan Ismangil Ngarfillah, Asep Nahrul Musadad (UNIVERSUM, 2016)
AbstractOne of the key terms employed in showing the connection between jarh wa ta’dīl discourse and Islamic sectarianism issues is bid’ah “heresy” and al-mubtadi’ “heretic transmitter”. Start on preliminary introduction to bid’ah conception in the context of jarḥ wa ta’dīl, this article discusses Ibn Ḥajar al-‘Asqalāni’s notions about the concept of heresy (bid’ah) and validity of heretic transmitter (riwāyat al-mubtadi’). Ibṇ Hajar was choosed here as the exponent of culmination in “ulūm al-hadītḣ” discourse in which the bid’ah notion was arguably reconsidered along with the still-functioning Islamic sectarianism polemic. It deals finally with “kafir” claims (takfīr) as the so-called “theological weapon” to blame others.Keywords; Ibnu Hajar al-‘Asqalāni, bid’ah, dan riwāyat al-mubtadi’